23 Small intestinal bacterial overgrowth in chronic pancreatitis patients with pancreatic exocrine insufficiency; a prospective cohort study. (5th April 2017) - Chonchubhair, H Ní; Bashir, Y; Dobson, M; Ryan, B; Duggan, S; Conlon, K
Abstract : Background: Pancreatic exocrine insufficiency (PEI) causes malabsorption and is a major complication of chronic pancreatitis (CP). Small intestinal bacterial overgrowth (SIBO) worsens symptoms and nutritional status in CP, its prevalence is unclear Aim: We examined SIBO prevalence in CP patients with PEI (defined as faecal elastase-1<200 ug/g) versus matched healthy controls. Method: 34 patients and 25 controls (matched for age/gender/smoking status) underwent hydrogen breath-testing using a glucose substrate. Exclusion criteria included gastric/pancreatic/intestinal surgery, or antibiotic treatment <4 weeks prior to study. Persistent rise in breath hydrogen 12 ppm above basal was diagnostic of SIBO. Results: Patients and controls were well-matched, with 67% and 64% males respectively (p=0.775), a mean (standard deviation) age of 52.4 (10.4) and 53.3 (10.5) year respectively (p=0.919), and 47.1% and 28% smokers respectively (p=0.143). Among patients, there was no association found between the presence of SIBO and gender (p=0.156), or PPI use (p=0.328). There was a significantly positive association found between the presence of SIBO and diabetes (p=0.033), while the positive association between the presence of SIBO and pancreatic enzyme replacement therapy (PERT) use just reached significance (p=0.052) Conclusions: SIBO prevalence was 15% and not associated with gender, age, or PPI use, but was positively associated with PERT use, and concurrent diabetes. Patients with diabetes may be more likely to suffer from SIBO due to small bowel dysmotility, whilst SIBO and PEI may co-exist, with similar symptoms. We recommend that SIBO should be considered in non-surgical CP patients, if they have gastro-intestinal symptoms that are unresponsive to high-dose PERT, particularly if there is co-existent diabetes. Treatment should be aggressive, and there may be a requirement for repeat therapy.